Respuesta :
P n ( given statement ) : 2 + 4 + 6 + ...+ 2 n = n · ( n + 1 )
P 1 : 2 = 1 · ( 1 + 1 )
2 = 2
P k : 2 + 4 + 6 + ... + 2 k = k · ( k + 1 )
P k+1 :
2 + 4 + 6 + ... + 2 k + 2 · ( k + 1 ) = k · ( k + 1 ) + 2 · ( k + 1 ) =
= ( k + 1 ) · ( k + 2 )
P 1 : 2 = 1 · ( 1 + 1 )
2 = 2
P k : 2 + 4 + 6 + ... + 2 k = k · ( k + 1 )
P k+1 :
2 + 4 + 6 + ... + 2 k + 2 · ( k + 1 ) = k · ( k + 1 ) + 2 · ( k + 1 ) =
= ( k + 1 ) · ( k + 2 )
Answer:
P(1) = 2, P(k) = 2k, P(k+1) = 2(k+1)
Step-by-step explanation:
The given statement is Pn = 2 + 4 + 6 +........+ 2n = n(n+1)
Now we have to write the statements P1, Pk, P(k+1)
P1 = 2
Pk = P1 + (n -1 ) d
Pk = 2 + (k -1)2 = 2 + 2k -2 = 2k
P(k+1) = Pk + 2
P(k+1) = 2k + 2 = 2(k+1)
Therefore the answers are
P1 = 2
P(k) = 2k
and P(k+1) = 2(k +1)